(untitled) (Research, Society and Development, 2023)
Classroom management includes the teacher’s actions in order to create and sustain a supportive and stimulating learning environment, through building up authentic relationships of interaction and cooperation with his/her students. The aim of this paper is to highlight the teacher’s key role in the challenge of the effective classroom management, as s/he has to cope with a highly heterogenous students’ population, his/her multifaced tasks and the dynamic changes in the educational field. The results showed that a successful classroom management is facilitated by the teacher’s professional readiness and his/her developed communication skills, who planning and organizing the educational process, according to students’ diverse educational needs and interests, providing them a high-quality educational work in a well-structured engaging and reflective learning environment and cultivating meaningful relationships of reciprocity, contributes, decisively, to their academic learning and socio-emotional development.